Advertising for Natural Beauty Products: The Shift in Cosmetic Industry - Lixandru, Mara-Georgia (European Scientific Journal, ESJ, 2017)
The following article aims to present and give an overview on the role played by advertisement for natural beauty products within the current social, environmental, and economic environment, taking into account the existing mechanism that regulates the current market and the way that the consumer is informed about specific products. Nowadays, the cosmetic industry returns to the “less is more” concept. As people have become increasing informed about potentially harmful chemicals in beauty products, they are learning to read labels of their skin-care products and cosmetics. Moreover, they have begun to recognize those substances less friendly to health and the environment, becoming more aware of what to avoid.